2011
DOI: 10.1007/s12603-010-0305-5
|View full text |Cite
|
Sign up to set email alerts
|

Country of origin predicts nutrition risk among community living older people

Abstract: Nutrition risk is common among aged individuals living in the community. Health and social factors that shape eating behaviours place older people at increased nutrition risk. Strategies are needed for the early identification of risk factors to prevent nutrition problems. Engaging older people at risk to share meal preparation and dining experiences may foster better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In addition, perceived helplessness was a predictor in the second regression analysis, which was also identified in a study by Tomstad et al10 These factors highlight the close relationship between lower self-care ability and risk of undernutrition 10,30,31,38. In other studies, functional dependency6,7,33 and disability12 have also been found to be related to risk of undernutrition. Consequently, physical impairment requires special attention 36…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, perceived helplessness was a predictor in the second regression analysis, which was also identified in a study by Tomstad et al10 These factors highlight the close relationship between lower self-care ability and risk of undernutrition 10,30,31,38. In other studies, functional dependency6,7,33 and disability12 have also been found to be related to risk of undernutrition. Consequently, physical impairment requires special attention 36…”
Section: Discussionsupporting
confidence: 72%
“…It has been found that advanced age,4–7 the presence of several comorbidities,5–7 hospitalization in the previous year,7 decline in intellectual activity,8 being functionally dependent,6,7 receiving help to manage daily life,7,9,10 and receiving meals on wheels11 are associated with undernutrition or risk of undernutrition among home-dwelling older people. Loss of a spouse,6,8,12 living alone,9,10 having a lower level of education,5 perceiving impaired health,7,9,11 and lowered quality of life7 are further factors found to be related to impaired nutritional status in older home-living people.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of at risk and high risk categories resulted in a prevalence of up to 62% (Southgate et al, 2010;Watson et al, 2010;Wham et al, 2011c). Living alone (McElnay et al, 2012;Ramage-Morin and Garriguet, 2013;Wham et al, 2011c), less social support (Ramage-Morin and Garriguet, 2013), depression (Ramage-Morin and Garriguet, 2013), poor self rated health (Wham et al, 2011a), disability (Wham et al, 2011a) and eating alone (Watson et al, 2010;Wham et al, 2011a) were identified as factors associated with malnutrition risk. Meanwhile, a higher mortality rate within 5 years was documented in the high nutritional risk group, compared to those in other groups (Broeska et al, 2013).…”
Section: Screen © IImentioning
confidence: 99%
“…SCREEN © II, an improved version of SCREEN © , identified 31-52% of individuals to be at high risk of malnutrition (Broeska et al, 2013;McElnay et al, 2012;Ramage-Morin and Garriguet, 2013;Wham et al, 2011a;Wham et al, 2011c). A combination of at risk and high risk categories resulted in a prevalence of up to 62% (Southgate et al, 2010;Watson et al, 2010;Wham et al, 2011c).…”
Section: Screen © IImentioning
confidence: 99%
“…Recent research estimates 31-60% of the older NZ population to be at high nutrition risk. [9][10][11] Dietitians apply robust scientific knowledge about food and nutrition to promote optimal health outcomes to individuals, groups and communities in states of both health and disease. Dietitians are registered health professionals who meet standards required by the NZ Dietitians Board under the NZ Health Practitioners Competence Assurance Act (HPCA) 2003.…”
Section: What Gap This Fillsmentioning
confidence: 99%